Civil Society Organisations: Filling Up The Government Service Gap For National Development - Akin, Popoola Michael; Adeola, Omosebi Fredrick (International Journal of Scientific Research and Management (IJSRM), 2018)
Good governance is inextricably linked with development. That is why any government which is genuinely concerned about good governance makes the issue of development its central focus. However, the governments of many developing countries experience capacity deficit in the area of the requisite institutions, funds and capacity to foster comprehensive socio-economic development. This makes it imperative for the state to engage in collaborative relationship with civil society which can help to fill up the lacuna created by the lack of state institutional and technical capacity. The critical role of civil society in development is aptly appreciated by some donor institutions and western countries which channel their Official Development Assistance (ODA) to developing countries through civil society organisations for effective implementation. This research therefore, undertakes an analysis of the way and manner which civil society organisations can complement the development efforts of the state. What makes this research crucial is the belief in some quarters that the state and civil society are often mutually conflicting and perpetually locked in zero sum game. However, this paper discovered that both the state and civil society are mutually reinforcing entities and that development is enhanced when there is collaborative efforts, rather than contestation  between them.